2012
DOI: 10.1101/gr.145144.112
|View full text |Cite
|
Sign up to set email alerts
|

The transcriptional landscape and mutational profile of lung adenocarcinoma

Abstract: All cancers harbor molecular alterations in their genomes. The transcriptional consequences of these somatic mutations have not yet been comprehensively explored in lung cancer. Here we present the first large scale RNA sequencing study of lung adenocarcinoma, demonstrating its power to identify somatic point mutations as well as transcriptional variants such as gene fusions, alternative splicing events, and expression outliers. Our results reveal the genetic basis of 200 lung adenocarcinomas in Koreans includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
415
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 533 publications
(438 citation statements)
references
References 51 publications
(63 reference statements)
20
415
3
Order By: Relevance
“…This exclusivity of lung adenocarcinoma driver alterations has been observed previously and is confi rmed in this large cohort of lung adenocarcinoma specimens. Tumors with MET ex14 alterations rarely harbored the other known drivers of lung adenocarcinoma, as has been previously observed in other cohorts (23)(24)(25)(26), supporting the role of MET ex14 alterations as oncogenic driver mutations. We also observed that mutations in KRAS , EGFR , ERBB2 , and MET each frequently co-occurred with copy-number amplifi cation of the same gene, highlighting the cumulative effect of gene activation by both mutation and amplifi cation.…”
Section: Resultssupporting
confidence: 82%
“…This exclusivity of lung adenocarcinoma driver alterations has been observed previously and is confi rmed in this large cohort of lung adenocarcinoma specimens. Tumors with MET ex14 alterations rarely harbored the other known drivers of lung adenocarcinoma, as has been previously observed in other cohorts (23)(24)(25)(26), supporting the role of MET ex14 alterations as oncogenic driver mutations. We also observed that mutations in KRAS , EGFR , ERBB2 , and MET each frequently co-occurred with copy-number amplifi cation of the same gene, highlighting the cumulative effect of gene activation by both mutation and amplifi cation.…”
Section: Resultssupporting
confidence: 82%
“…To date, MET exon 14 oncogenic alterations have been reported in approximately the 4% of lung cancer (25)(26)(27). According to the Cancer Genome Atlas (TCGA) project, the 4.3% of lung adenocarcinoma harbors DNA alterations with MET exon 14 skipping, confirmed by RNA analysis (28).…”
Section: Lung Cancermentioning
confidence: 99%
“…ROS1 is fused to one of a number of genes in lung cancers, including CD74, SLC34A2, EZR, LRIG3, SDC4, TPM3, FIG (also known as GOPC), CCDC6, and KDELR2. [4][5][6][7][9][10][11][12] In these fusions, the 3 0 region of ROS1 encoding its kinase domain is fused to the 5 0 region of the respective partner gene. The fusion encodes a chimeric protein with constitutive kinase activity that initiates oncogenic intracellular signal transduction cascades.…”
mentioning
confidence: 99%